Metformin after Bariatric Surgery – an Acid Problem - Aberle, J.; Reining, F.; Dannheim, V.; Flitsch, J.; Klinge, A.; Mann, O. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Metformin is the oral drug of first choice in type 2 diabetes. Therefore a large number of patients undergoing bariatric surgery will be on Metformin treatment. However, use of Metformin has been associated with lactate acidosis. Weight loss following bariatric surgery is most pronounced during the first weeks after the operation and this creates a phase of negative energy balance with ketone body formation. To shed more light on this situation we measured ketone bodies in 90 patients 5 days–18 months after bariatric surgery. Ketone bodies were markedly elevated during the first 3–4 months. Metformin use should therefore be critically reconsidered after bariatric operations.
Keywords: obesity; fatty acid synthesis; metabolic surgery